The engagement of social media technologies by undergraduate informatics students for academic purpose in Malaysia. Issue 3 (2014) - ,; ,; ,; ,
Abstract : Purpose – This study aims to investigate the perceptions, acceptance, usage and access to social media by students and academics in higher education in informatics programs in Malaysia. A conceptual model based on Connectivism and communities of practice (CoPs) learning theory was developed and were used as a basis of mapping the research questions to the design frameworks and the research outcomes. A significant outcome of this study will be the development of a design framework for implementing social media as supporting tools for student engagement and teaching and learning of informatics programs in higher education institutions (HEIs) in Malaysia.Design/methodology/approach – A mixed‐method research methodology with a significant survey research component was employed for this research. This methodology focused on collecting and analyzing quantitative and qualitative data to better understand the research problems. For this study, a mixed‐method sequential transformative research strategy based on a QUAN‐Qual model was used in the data collection process. Mixed‐method research methodology is considered to be most appropriate for this study, as it allows the researcher to gather multiple forms of data from diverse audiences such as educators, administrators and students.Findings – The findings show the close matched of the ownership, amount of hours spent online, types of social media technologies (SMTs) used and pattern of usage between informatics and non‐informatics students. It also shows that many students and instructors have started to explore and accept the use of SMTs as a tool for engaging with their institution and their peers as well as for teaching and learning purposes. Innovative institutions need to understand the critical success factors and the barriers that restrict the implementation of SMTs within the HEI to take advantage of the opportunities offered by SMTs in higher education.Research limitations/implications – The surveys and interview participant, in part, are self‐selecting, so the data collected cannot be claimed to be representative of the population. However, because of the relatively large number of participants, it can be considered that the findings are indicative. Other limitation includes the depth of data that can be collected using this methodology.Practical implications – There is wide range of social media usage in educational settings now being reported, but many issues are still unexamined. Limited studies have been focusing on the educators' readiness, acceptance or refusal in integrating social media into their courses, the perceived effectiveness of the tools and student outcomes for their learning. The central outcome of this research will be the development of a design framework that will be used as a guide for Malaysian HEIs and informatics academics to engage students using SMTs in creating effective learning communities for informatics programs.Social implications – The framework will have implication for the social interaction and engagement of students with their institution.Originality/value – Very little work has been reported on student and academic engagement, their perspectives and perceived effectiveness of social media usage in higher education, especially in the Malaysia context. Most of the research focused only on the quantitative research with students from universities in the USA and Australia, with an emphasis mainly on student's perception and acceptance. There are calls for more research to examine how social media is perceived and accepted by students and academics for teaching and learning, especially in Malaysia.